Beyond lectures and practical courses: Teaching pharmacology using imaginative pedagogical tools - J.E. Baños; E. Blanco-Reina; I. Bellido-Estévez; F. Bosch; M.R. Cabello; I. Cambra-Badii; J.P. De la Cruz; P. D'Ocón; M.D. Ivorra; M. Ferrándiz; J.A. González-Correa; E. Martín-Montañez; et al. (Elsevier, 2024)
Pharmacology has broadened its scope considerably in recent decades. Initially, it was of interest to chemists, doctors and pharmacists. In recent years, however, it has been incorporated into the teaching of biologists, molecular biologists, biotechnologists, chemical engineers and many health professionals, among others. Traditional teaching methods, such as lectures or laboratory work, have been superseded by the use of new pedagogical approaches to enable a better conceptualization and understanding of the discipline. In this article, we present several new methods that have been used in Spanish universities. Firstly, we describe a teaching network that has allowed the sharing of pedagogical innovations in Spanish universities. A European experience to improve prescribing safety is described in detail. The use of popular films and medical TV series in biomedical students shows how these audiovisual resources can be helpful in teaching pharmacology. The use of virtual worlds is detailed to introduce this new approach to teaching. The increasingly important area of the social aspects of pharmacology is also considered in two sections, one devoted to social pharmacology and the other to the use of learning based on social services to improve understanding of this important area. Finally, the use of Objective Structured Clinical Evaluation in pharmacology allows to know how this approach can help to better evaluate clinical pharmacology students. In conclusion, this article allows to know new pedagogical methods resources used in some Spanish universities that may help to improve the teaching of pharmacology.